Cara Pintar Mengelola Keuangan Keluarga Bagi Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan (PKH) - Misfi Laili ifi (Randang Tana - Jurnal Pengabdian Masyarakat, 2024)
The problem of poverty is still a homework that has not been resolved by the government. Various efforts have been made, one of which is through the Family Hope Program (PKH), which is a conditional cash assistance for beneficiaries. It is said to be conditional because recipients must access education and health services using the grant funds received. However, based on information obtained from the companion, it is known that the recipients did not fully use the aid money according to its designation. This happens for various reasons, one of which is minimal income so they have to look for other sources to meet their daily needs. Therefore, this dedication is intended to provide an understanding of how to manage family finances so that whatever income is earned can be sufficient to meet life's needs, not a lifestyle. This dedication method is carried out with lectures, discussions and brainstorming with participants. The result of this service is that participants gain additional knowledge about budget planning, budget control, and distinguishing between needs and wants